1999
DOI: 10.1088/0026-1394/36/5/2
|View full text |Cite
|
Sign up to set email alerts
|

The nanometric roughness of mass standards and the effect of BIPM cleaning-washing techniques

Abstract: A method based on light scattering has been used to characterize the surface roughness of four standard kilograms made from XSH alacrite, in order to determine the root-mean-square height and the correlation length . The values of these two parameters, which have been found to lie between 2 nm and 5 nm and between 170 nm and 250 nm, respectively, show the high surface quality that it is possible to obtain by mechanical polishing of XSH alacrite. Cartographies made by light scattering, as well as and values, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
1
8
0
1
Order By: Relevance
“…Results from ultrasonic cleaning in ethanol (figure 2) show that contamination was removed mainly from the grooves, which arise from machining of stainless steel. This result agrees with Zerrouki et al [21], who suggested that initial cleaning removes fine particles and dust from scratches in the surface. The contamination that was removed is assumed to be carbonaceous contamination, which has accreted on the surface during the years.…”
Section: Discussionsupporting
confidence: 92%
“…Results from ultrasonic cleaning in ethanol (figure 2) show that contamination was removed mainly from the grooves, which arise from machining of stainless steel. This result agrees with Zerrouki et al [21], who suggested that initial cleaning removes fine particles and dust from scratches in the surface. The contamination that was removed is assumed to be carbonaceous contamination, which has accreted on the surface during the years.…”
Section: Discussionsupporting
confidence: 92%
“…Storage conditions (air, vacuum, inert gas) and cleaning methods (alcohol, UV/Ozone, plasma, or thermal desorption) are also factors that affect mass stability. [12][13][14][15][16][17] To understand how surface behaviour affects mass stability after the artefact has been cleaned using different methods and stored under different conditions, it is essential to characterize surface quality by rugosimetric methods (for example, optical scatterometer or X-ray reflectometer, SNOM, or atomic force microscopy 18,19 ) to evaluate mass stability by gravimetric methods by means of mass comparators as well as to identify surface contaminants using spectrometric techniques (for example, XPS (X-Ray photoelectron spectrometry) or ToF-SIMS (Time-of-Flight Secondary ion mass spectrometry)).…”
Section: B Mass Stability and Surface Characterizationmentioning
confidence: 99%
“…The initial loss in mass is generally much larger than subsequent changes. Zerrouki et al [13] have suggested that the initial cleaning removes fine particles and dust from holes and scratches in the surface.…”
Section: Resultsmentioning
confidence: 99%